2021
DOI: 10.2147/ndt.s333753
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Homocysteine, Inflammation and Cognitive Impairment in Patients with Acute Ischemic Stroke and Transient Ischemic Attack

Abstract: Purpose To investigate the associations among homocysteine (Hcy), inflammation and cognitive impairment in patients with acute ischemic stroke (AIS) and transient ischemic attack (TIA). Patients and Methods Patients included were enrolled from a subgroup of China National Stroke Registry-III (CNSR-III). We used a Chinese version of Montreal Cognitive Assessment (MoCA) to screen for cognitive impairment. We used high-sensitivity C-reactive protein (hsCRP) level to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…While we found that no singular comorbid condition was associated with post-stroke cognitive decline, as measured by MoCA or MMSE, the total scores were associated with cognitive decline and, therefore, may be indicative of a cumulative, rather than singular, burden. This is not an entirely novel finding in the literature [ 24 , 25 ]; however, the perspective in the literature, when it comes to correlations between disease states and cognitive function, is quite narrow. For example, studies often illustrate the differences in cognitive outcomes, depending on singular inflammatory conditions, such as diabetes [ 26 ], metabolic syndrome [ 27 ], obstructive sleep apnea [ 28 ], and hypertension [ 14 , 29 ], rather than a collective burden of multiple comorbid conditions.…”
Section: Discussionmentioning
confidence: 71%
“…While we found that no singular comorbid condition was associated with post-stroke cognitive decline, as measured by MoCA or MMSE, the total scores were associated with cognitive decline and, therefore, may be indicative of a cumulative, rather than singular, burden. This is not an entirely novel finding in the literature [ 24 , 25 ]; however, the perspective in the literature, when it comes to correlations between disease states and cognitive function, is quite narrow. For example, studies often illustrate the differences in cognitive outcomes, depending on singular inflammatory conditions, such as diabetes [ 26 ], metabolic syndrome [ 27 ], obstructive sleep apnea [ 28 ], and hypertension [ 14 , 29 ], rather than a collective burden of multiple comorbid conditions.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have revealed that systemic inflammation processes are closely related to endothelial dysfunction, cell death, blood-brain barrier (BBB) disruption, cerebral blood flow autoregulation disorder and platelet aggregation [ 5 , 13 ]. Studies consecutively showed that PSCI was associated with some inflammatory biomarkers and cytokines [ 14 , 15 ]. Otherwise, as important primary immune mediators that can release inflammatory signals, infiltrating leukocytes, including neutrophils, monocytes, and lymphocytes, have been reported to be related to stroke and dementia [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is a sulfur-containing amino acid produced during methionine metabolism, which generates oxygen radicals with strong oxidative effects on vascular endothelial cells and is defined as a reactive vascular damage amino acid ( 32 ). High Hcy can cause endothelial dysfunction in the body and plays an important role in the pathogenesis of neurological disorders such as stroke and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%